(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
in the study of differential equations in the article, the disclosure of certain aspects of the "Matematica" package is seen as the main problem. In solving the equations of Bernoulli, Cleero and Riccati, examples are given on the possibilities of the "Matematica" package.